PENGEMBANGAN MEDIA PEMBELAJARAN DIORAMA HUJAN BUATAN (DIHUBA) SEBAGAI MEDIA PEMBELAJARAN SIKLUS AIR DI SEKOLAH DASAR - Aqilah Naurah; Tunjungsari Sekaringtyas; Arita Marini (STKIP Subang, 2026)
ABSTRACT The water cycle is one of the science topics in elementary schools that is considered difficult for students to understand because several processes are abstract and cannot be observed directly. In addition, the limited use of learning media causes students to be less enthusiastic during the learning process. This study aimed to develop a learning medium called Diorama Hujan Buatan (DIHUBA) and determine its feasibility for teaching the water cycle concept to fifth-grade elementary school students. The research employed a Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through observation, interviews, questionnaires, and expert validation sheets involving media, material, and language experts. The developed product was also tested on students through one-to-one, small-group, and field-test trials. The results showed that the media expert validation score reached 94.67%, material expert validation 94.00%, and language expert validation 98.00%, with an average feasibility score of 95.56%, categorized as very feasible. Student trials obtained scores of 96.89% in one-to-one testing, 97.87% in small-group testing, and 97.73% in field testing, with an average of 97.69%, categorized as very feasible. Therefore, the DIHUBA learning media is highly feasible to be used as an innovative learning medium to help students understand the water cycle concept more concretely and meaningfully.